Tinjauan Psikologi Pengendalian Emosi Sedih Dalam Al-Qur’an: Menurut Penafsiran Asy-Sya’rawi terhadap QS Yūsuf Ayat 86 - Rahmansyah, Andi; Anwar, Husnel; Munandar (Al-Wasathiyah: Journal of Islamic Studies, 2023)
In people's lives as social beings, interaction with others is a necessity. Not infrequently this interaction can lead to various types of anger. Anger inside people is very diverse and has a fairly large range, that's why until today experts have not made an agreement regarding the interpretation of anger in the usual way. One of them is the definition of anger put forward by Robert C. Judging from the type of research, there is also a type of research used in this research, namely bibliography research or library research, which is research that is carried out by collecting information or making objective notes with the aim of the research object. or collection of information in the nature of a bibliography, or analysis carried out to uncover a problem which is basically based on critical and in-depth analysis of relevant literature materials. This research results that related to the problem that the author has presented in chapter I, the author obtains three phases of controlling sad emotions according to the Alqurān surah Yūsuf verse 86 with theoretical analysis from M. Darwis Hude and its implementation form with a psychological approach Controlling the sad emotions of Prophet Ya'qūb in interpretation Surah Yūsuf verse 86 can only be fully understood by looking at the background of the Prophet Ya'qūb's sadness as set forth in the previous verses (80-85), then the core verses (86), and the verses after (87). Keywords: